The Sleepy Teenager – Diagnostic Challenges - Landtblom, Anne-Marie; Engström, Maria (Frontiers in Neurology, 2014)
The sleepy teenager is a diagnostic challenge because the problems may be physiological or pathological, with behavioural, social and pychological expressions. It is of great importance that health staff that encounter young people with sleep disturbance have good knowledge about the diseases that must be excluded. Narcolepsy, periodic hypersomnia like Kleine Levin syndrome, delayed sleep phase syndrome and obstructive sleep apnoea syndrome, depression and substance use as well as fatigue from chronic disease like multiple sclerosis should be investigated. Clinical assessment, neurophysiological and laboratory investigations constitute important support in these investigations. Functional methods, for example fMRI, are being developed. The role of computer gaming and use of social media in the night is discussed in relation to these diseases. Cognitive dysfunction may develop with several of the conditions. There is need for increased awareness of how to investigate sleep disturbance in children and young people.